ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERASI - anggina; Sucipto, Agus (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of Liquidity, Profitability and Leverage on Stock Returns with Firm Value as a moderating variable in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The research method is descriptive quantitative, namely an explanation of the number measurement system, and the data obtained for conducting the research is taken through the financial reports of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The number of samples obtained in this study were 11 companies taken from companies in the food and beverage sub-sector group of companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2021 period. The results and conclusions found are that the liquidity ratio proxied by the current ratio has no significant effect on stock returns, the profitability ratio proxied by return on assets has a significant negative effect on stock returns, the leverage ratio proxied by the debt equity ratio has no effect significantly to stock returns, firm value proxied by price to book value is not able to moderate the current ratio to stock returns, firm value proxied by price to book value is able to moderate the return on assets on stock returns, and firm value proxied with price to book value unable to moderate the debt equity ratio to stock returns.